A new freshwater ricefish of genus Oryzias (Teleostei: Adrianichthyidae) from northern Taiwan - Chen, I-Shiung; Yeh, Ming-Fon; Lai, Hong-Thih (Zootaxa, 2025)
A new freshwater ricefish was collected recently from northern Taiwan, which has been identified as a species new to science. The new species, Oryzias cabaranensis sp. nov., can be well distinguished from other congeners by the following unique combination of features: (1) fin-ray counts: dorsal-fin rays 6; anal-fin rays modally 17; pectoral-fin rays 9–10; (2) body compressed laterally, body depth at pelvic origin 20.9–23.3 (22.3), body depth at anal fin origin 17.2–20.1 (18.8); (3) the dorsal-fin origin inserted almost at the vertical of 12th anal-fin rays; and (4) specific coloration: Body translucent, light creamy yellowish, a dotted, longitudinal black line. Belly wall, peritoneum slivery, somewhat subrectangular. Operculum and pre-pectoral region slivery. Eye light bluish. Caudal fin unmarked. Pelvic and anal fins with tiny melanophores. The diagnostic characters and a comparison with related species will also be provided.